The Thermic Effect of Food: A Review. (18th August 2019) - Calcagno, Manuel; Kahleova, Hana; Alwarith, Jihad; Burgess, Nora N.; Flores, Rosendo A.; Busta, Melissa L.; Barnard, Neal D.
Abstract: Two-thirds of U.S. adults are overweight. There is an urgent need for effective methods for weight management. A potentially modifiable component of energy expenditure is the thermic effect of food (TEF), the increase in the metabolic rate that occurs after a meal. Evidence suggests that TEF is increased by larger meal sizes (as opposed to frequent small meals), intake of carbohydrate and protein (as opposed to dietary fat), and low-fat plant-based diets. Age and physical activity may also play roles in TEF. The effects of habitual diet, meal timing, and other factors remain to be clarified. Further research into the factors that affect TEF may lead to better treatment methods for improved weight management. Key teaching points: Measurement of the thermic effect of food. Physiological determinants of the thermic effect of food. The effects of meal variations on postprandial thermogenesis. Effect of age and physical activity on the thermic effect of food.